Whole-exome sequencing identifies a novel germline variant in PTK7 gene in familial colorectal cancer - Miao, Beiping; Skopelitou, Diamanto; Srivastava, Aayushi; Giangiobbe, Sara; Dymerska, Dagmara; Paramasivam, Nagarajan; Kumar, Abhishek; Kuświk, Magdalena; Kluźniak, Wojciech; Paszkowska-Szczur, Katarzyna; Schlesner, Matthias; Lubinski, Jan; et al. (International journal of molecular sciences, 2022)
Colorectal cancer (CRC) is the third most frequently diagnosed malignancy worldwide. Only 5% of all CRC cases are due to germline mutations in known predisposition genes, and the remaining genetic burden still has to be discovered. In this study, we performed whole-exome sequencing on six members of a Polish family diagnosed with CRC and identified a novel germline variant in the protein tyrosine kinase 7 (inactive) gene (PTK7, ENST00000230419, V354M). Targeted screening of the variant in 1705 familial CRC cases and 1674 healthy elderly individuals identified the variant in an additional familial CRC case. Introduction of this variant in HT-29 cells resulted in increased cell proliferation, migration, and invasion; it also caused down-regulation of CREB, p21 and p53 mRNA and protein levels, and increased AKT phosphorylation. These changes indicated inhibition of apoptosis pathways and activation of AKT signaling. Our study confirmed the oncogenic function of PTK7 and supported its role in genetic predisposition of familial CRC.
Gesehen am 12.04.2022
This article belongs to the Special Issue Linking Genomic Changes with Cancer in the NGS Era